Pragmatics Approach in Teaching “Maharah Kalam” at Pondok Modern Darul Hikmah Tulungagung - Mohamad Jazeri; Kojin Kojin; Dwi Astuti Wahyu Nurhayati (IAIN MADURA, 2018)
Speaking proficiency, maharah kalam, is one of the Arabic teaching goals at Pondok Modern Darul Hikmah Tulungagung. Speaking skill will be better mastered by the understanding of language usage in the daily communication context. Therefore, Pragmatics approach is fruitfully employed in teaching speaking skill. This study aims at describing the Pragmatics approach in teaching speaking skill at Pondok Modern Darul Hikmah Tulungagung. This study belonged to queasy experiment. Data were collected through doing participation-observation, interview, and test. The result of data analysis revealed that Pragmatics approach in teaching Arabic speaking skill in Pondok Modern Darul Hikmah was reflected in the instructional design. This approach was implemented through three programs, namely dialogue (al-hiwar), pattern practice (tathbiq al-namudzaj), and oral practice (tarkib al-syafawi). In addition, there was a significant difference result of pre-test and post-test. It was assumed as an effect of applying pragmatics approach in teaching maharah kalam at Pondok Modern Darul Hikmah Tulungagung.